Intermediate GNVQ construction and the built environment - Millward, Des; Attfield, Jeff; Ahmet, Kemal (Longman GNVQ, 1997)
This book, written by GNVQ specialists, covers everything that students need to know, prepare and revise, for their GNVQ qualifications. It includes unit tests, self-check questions and answers & offers advice on compiling the portfolio of evidence.